Solution processable organic/inorganic hybrid ultraviolet photovoltaic detector - Guo, Xiaopeng; Tang, Libin; Xiang, Jinzhong; Ji, Rongbin; Zhang, Kai; Lai, Sin Ki; Zhao, Jun; Kong, Jincheng; Lau, Shu Ping (AIP advances, 2016)
Ultraviolet (UV) photodetector is a kind of important optoelectronic device which can be widely used in scientific and engineering fields including astronomical research, environmental monitoring, forest-fire prevention, medical analysis, and missile approach warning etc. The development of UV detector is hindered by the acquirement of stable p-type materials, which makes it difficult to realize large array, low-power consumption UV focal plane array (FPA) detector. Here, we provide a novel structure (Al/Poly(9,9-di-n-octylfuorenyl-2,7-diyl)(PFO)/ZnO/ITO) to demonstrate the UV photovoltaic (PV) response. A rather smooth surface (RMS roughness: 0.28 nm) may be reached by solution process, which sheds light on the development of large-array, light-weight and low-cost UV FPA detectors.